PENGARUH LATIHAN 10-CONE SNAKE DRILL TERHADAPKELINCAHAN PADA PEMAIN SEPAK BOLA SSB GENARIPEKANBARU - Sentono, Ario Sentono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This study was conducted to determine whether there are effects of exercise on the 10-cone snake drill against agility the footballplayers to get maximum result when playing football. This research is a form of research with experimental treatment (Experimental), with a population of athletessoccer school genari pekanbaru,in this study all populationsample of 17 people. The instruments used in this research is dogging run test, which aims to measure the agility. Afterthat, data is processed with statistics, to the test normality of the test at significant level 0,05Î± lilifors. Hypothesis proposed, exercise effect of10-cone snake drill to agility.Based on t test analysis produces10,76 Thitung and 1.764 Ttabel, its meansThitung>Ttabel. Based on analysis of statistical data, there are on Pree-testaverage was 11,296 andpost-testaverage was 10,342, data is normal. Then Ha go through, there is a Exercise Effect of 10-cone snake drill against agility in soccer schoolplayers of genari Pekanbaru. Keywords: 10-cone snake drill, agility